2005
DOI: 10.1101/gad.1269305
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae imports the cytosolic pathway for Gln-tRNA synthesis into the mitochondrion

Abstract: Aminoacyl-tRNA (aa-tRNA) formation, an essential process in protein biosynthesis, is generally achieved by direct attachment of an amino acid to tRNA by the aa-tRNA synthetases. An exception is Gln-tRNA synthesis, which in eukaryotes is catalyzed by glutaminyl-tRNA synthetase (GlnRS), while most bacteria, archaea, and chloroplasts employ the transamidation pathway, in which a tRNA-dependent glutamate modification generates Gln-tRNA. Mitochondrial protein synthesis is carried out normally by mitochondrial enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 47 publications
3
102
1
Order By: Relevance
“…One could suggest therefore that inhibited or perturbed translation (appearance of additional translation products) is due to a decrease of imported tRK1. This is in agreement with our previous observation of suppression of a mtDNA mutation by imported tRNAs (Kolesnikova et al 2000) and with a more recent hypothesis suggesting the need of several cytoplasmic tRNAs to provide a complete decoding in yeast mitochondria (Rinehart et al 2005). It may occur that we obtained here the first evidence that, at least at higher temperature, tRK1 is recruited by mitochondrial translation machinery.…”
Section: Enolase Another Protein With Multiple Functionssupporting
confidence: 82%
See 1 more Smart Citation
“…One could suggest therefore that inhibited or perturbed translation (appearance of additional translation products) is due to a decrease of imported tRK1. This is in agreement with our previous observation of suppression of a mtDNA mutation by imported tRNAs (Kolesnikova et al 2000) and with a more recent hypothesis suggesting the need of several cytoplasmic tRNAs to provide a complete decoding in yeast mitochondria (Rinehart et al 2005). It may occur that we obtained here the first evidence that, at least at higher temperature, tRK1 is recruited by mitochondrial translation machinery.…”
Section: Enolase Another Protein With Multiple Functionssupporting
confidence: 82%
“…targeted, tRNA Gln (Rinehart et al 2005) and tRNA Lys CUU (further referred to as tRK1) (Martin et al 1979), whose import appears to proceed by different mechanisms. Mitochondrial functions of tRK1 are not completely clear, although our previous results demonstrated that its mutant versions are functional in mitochondrial translation, since they are able to suppress a nonsense mutation in mitochondrial DNA-localized gene (Kolesnikova et al 2000).…”
mentioning
confidence: 99%
“…For glutamine (Gln), only one expressed cytosolic GlnRS was found. This observation is in accordance with the fact that Gln-tRNA Gln formation was shown to occur by transamidation in chloroplasts, and led to the suggestion that the same route of Gln-tRNA synthesis is also prevalent in mitochondria, although it has been shown in yeast that the cytosolic GlnRS is imported into mitochondria and is involved in mitochondrial Gln-tRNA Gln formation (17).…”
Section: Forty-five Expressed Aars Genes Were Found In the A Thalianasupporting
confidence: 55%
“…does not form Glu-tRNA Gln ) and the cytoplasmic GlnRS is present in the yeast mitochondria suggests a Glu-AdT is also not required in the organelle. 60 The conservation of the important residues in Pet112 for the kinase activity of GatB and GatE indicates a catalytic role for the enzyme in the cell.…”
Section: Alternative Function(s) For the Gatcab Subunit?mentioning
confidence: 99%